Creating an Autonomous Hovercraft for Bathymetric Surveying in Extremely Shallow Water (<1 m) - Meghan L. Troup; Matthew Hatcher; David Barclay (Sensors, 2023)
Coastal shallow water environments (<5 m) are extremely biodiverse and dynamic yet are often mapped too infrequently or at too low resolutions to capture the important processes occurring in these regions. Common forms of coastal surveying can leave gaps in data in the shallow water zone due to optical instrument capabilities and a vessel’s ability to navigate in this region. One solution to these issues is an autonomous hovercraft that can fly over land and water and begin surveying at sub-meter water depths, bridging the gap between common optical and acoustic surveying methods. The craft’s autonomy is tested via four autonomous flight paths, or missions, and the desired path is compared to both the observed heading and direction of motion. Although the accuracy for each track in the mission varies, most headings and directions of motion of the hovercraft are within 50 degrees of the desired direction. A single-beam echo sounder was used to map the bathymetry of the study site, showing a gently sloping beach.